Decomposition Rate of Avicennia lanata in Bakau Kecil Mangrove Forest Area, Mempawah District - Ashari, Asri Mulya; Warsidah, W. (BERKALA SAINSTEK, 2021)
Avicenna lanata is a type of mangrove that dominates the Mempawah Kecil Mangrove Forest. As many as 10 bacterial genera were identified from station 1 which is close to the influence of sea water, and 8 bacterial genera from station 2 which are close to residential areas. This study aims to determine the rate of decomposition of A. lanata leaf litter with 4 observation time periods with an interval of 15 days, namely the 15th, 30th, 45th and 60th days. The observations show that the rate of decomposition of the litter on the 15th day of observation is higher. Namely 0.206 gram/day at station I and 0.19 gram/day at station II, while the lowest rate of decomposition of litter occurred on the 60th day of observation, namely 0.112 gram/day at station I and 0.106 gram/day at station II. In addition, the parameters of physical and chemical of the environment such as DO, temperature, pH and salinity are in the range of their optimum values.